Towards a Holistic Framework in Fostering Spirituality at Work - TAN, Gilbert (Institutional Knowledge at Singapore Management University, 2007)
Management theories are shaped by the assumptions of man. The Scientific and Administrative School of Thoughts adopt a mechanistic view of human. The Human Relations School views humans as social beings. Spirituality at work looks at the spiritual side of the organization and views an as a spiritual being. This paper proposes a holistic framework to spirituality at work. Taking a systems approach the framework discusses how training, cultural and structural interventions directed the four sub-systems of the organization, namely, culture, leadership, structure and people, help to promote spirituality at work. The framework also discusses the organizational and individual outcomes of spirituality at work.